Effect of Charcoal on the Quality of Vermicompost Produced With Water Hyacinth and Cow Manure - Solomon Girmay Berhe; Ali Seid; Berhanu Abraha Tsegay; Shinjiro Sato; Getahun Yemata Lule (The Scientific World Journal)
The significance of water hyacinth (Pontederia crassipes (C. Mart.) Solms (Pontederiaceae) vermicomposting lies in its ability to effectively manage its invasiveness while also improving soil fertility and supporting sustainable agricultural practices. This study evaluates the effects of charcoal addition on the composting followed by the vermicomposting of water hyacinth (WH) and cow manure, focusing on the growth, reproduction, and survival of Eisenia fetida earthworms and the quality of the resulting vermicompost. The treatments included WH and cow manure (2:1) with 7.5% charcoal (T1), 5% charcoal (T2), and without charcoal (T3). Composting (30 days) followed by vermicomposting (60 days) was conducted in a controlled greenhouse environment. Samples were collected biweekly to analyze temperature, moisture, pH, electrical conductivity, total nitrogen, total available phosphorous, and total potassium contents, vermicompost yield, and earthworm growth parameters throughout the process. Results showed that T1 and T2 significantly improved earthworm weight (8.23–16.0%), number of earthworms (65.0–69.0%), cocoon production (37.0–49.0%), and hatchling count (49.0–77.6%), compared to T3 (control). Also, T1 and T2 increased pH (4.30–5.75%), total nitrogen (53.6–62.5%), total available phosphorus (61.6–117%), and total potassium (47.5–71.3%) and reduced electrical conductivity (9.91%), total organic carbon (17.9–42.1%), carbon: nitrogen ratio (46.5–64.4%), and vermicompost mass (22.0–28.3%) at the end of the vermicomposting period, compared to T3. Moreover, T1 and T2 exhibited significantly higher lettuce seed germination (92.4–93.5%), germination index (76.2–80.4%), shoot elongation (46.0–92.5%), and root elongation (9.00–15.0%), compared to T3. However, in most of the results, there was no significant difference between T1 and T2. This finding suggests that the use of T2 (5.00%) charcoal addition enhances vermicompost quality to optimal maturity and stability.